A case of thrombotic microangiopathy of unknown aetiology, clinically presenting as an acute surgical abdomen. Issue 11 (28th November 2019) - Stratford, Lydia Madeleine Isabel; Nahoor, Isaac; Dos Santos, Kataryna; Dos Santos, Antonio Alves
Abstract : A 48-year-old woman presented with severe abdominal pain, bilious vomiting and bloody diarrhoea for 1 day. On examination, she was haemodynamically unstable, febrile and clinically had an acute surgical abdomen. She had markedly raised inflammatory markers, neutrophils and deranged renal function. A CT abdominal scan revealed severe colitis and thickening throughout the length of the colon. The patient was stabilised and underwent emergency laparotomy resulting in total colectomy and end ileostomy formation. Postoperatively, she required several units of human albumin solution, red blood cell transfusions and octaplex (prothrombin complex) to prevent further bleeding. An inpatient haematology review revealed a hypocomplementaemia (C3/C4), low immunoglobulin (IgG, IgM, IgA) and peripheral blood films revealed schistocytosis indicating microangiopathic haemolytic anaemia. Bowel histology supported this, demonstrating circumferential lymphocytic phlebitis with thrombi and mucosal haemorrhage, necrosis and ulceration. The patient went on to suffer multiple ischaemic strokes before undergoing plasmapheresis, subsequent rehabilitation and making a successful recovery.